Schiaparelli & The Artists. - Blum, Dilys; Talley, André leon; Lacroix, Christian; Albrecht, Donald (New York : Rizzoli, 2017)
Warhol, Andy, Raoul, Dufy ; Dali, Salvador ; Fini, Leonor ; Beaton, Cecil ; Triolet, Elsa ; Cocteau, Jean
boek